PENDEKATAN KONTEKSTUAL, PENGETAHUAN AWAL SISWA, DAN HASIL BELAJAR IPA DI SMP - -, Sudiah -; -, Sjarkawi -; -, Emosda - (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2011)
The purpose of this study is to investigate effect of contextual approach and students’ prior-knowledge on students’ achievement in natural science. The contextual approach and students’ prior-knowledge are the independent variables, and the dependent variable is students’ achievement. Samples of the research are 68 grade 8-th students of SMP 10 Muara Jambi which are divided into two groups. The first group is experimental group taught by using contextual approach and the second is  control group. Based on Two-way ANOVA analysis and Tukey analysis it can be shown that there is significant effect of contextual approach and students’ prior-knowledge on their achievement in natural science. Keywords: contextual approach, prior-knowledge, students’ achievement , natural science